O idoso no contexto do exercício físico - João Pedro Osório Silva (2017)
This report intent to expose the work done during the last academic year, involving exercise programs with different elderly groups. The internship was developed with 2 groups of the Faculty of Sports of the University of Porto, namely strength training group and multicomponent group and in some others partnership institutions such as "Obra Diocesana de Promoção Social" and "União de Freguesias de Aldoar, Foz do Douro and Nevogilde" with the "Trajectórias" project. This report reflects in detail all of the experiences and difficulties felt during the practical context of physical exercise sessions, which took me to make decisions about the path to follow in the different contexts. Furthermore, it also describes the different elderly groups that we have worked with during this year, the context and the reality in which they were inserted and their main characteristics. I would like to highlight that these activities shouldn't be seen in an isolated way, but as an important mean to achieve a particular purpose, which in this case was our training and evolution as a future teacher.